PENGARUH PENGAWASAN LASHING TERHADAP EFEKTIVITAS LASHING PETI KEMAS DI KM.KENDHAGA NUSANTARA 6 - Rafsanjani, Nanda Ayu; Sukirno, Sukirno; Ismail, Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the critical issue of container cargo security on ships, where inadequate supervision of the lashing system often leads to loosened bindings, shifting containers, and heightened maritime safety risks. The purpose of this research is to evaluate the significance of the influence of lashing supervision on the effectiveness of container lashing on KM Kendhaga Nusantara 6. Lashing supervision involves inspections and maintenance based on the Cargo Securing Manual (CSM), while lashing effectiveness is measured by cargo stability and the prevention of damage. Employing a quantitative explanatory design, primary data were gathered through a Likert scale questionnaire administered to 20 crew members, including the captain and ship officers, using a total sampling technique. Data analysis was performed using descriptive statistics, classical assumption tests, and simple linear regression analysis. The results of the simple linear regression analysis revealed a highly strong and positive relationship between the variables (R = 0.992). Lashing supervision was found to contribute 98.4% to lashing effectiveness (R² = 0.984), as formulated by the regression equation Y = -0.627 + 0.692X. Furthermore, the partial t-test confirmed that lashing supervision has a positive and statistically significant effect on lashing effectiveness (t = 33.008, Sig. = 0.000 < 0.05). In conclusion, more structured and consistent lashing supervision substantially ensures higher container securing efficiency and ship operability safety on KM Kendhaga Nusantara 6.